Epidemiology of 3825 injuries sustained in six seasons of National Collegiate Athletic Association men's and women's soccer (2009/2010–2014/2015). Issue 13 (17th May 2016) - Roos, Karen G; Wasserman, Erin B; Dalton, Sara L; Gray, Aaron; Djoko, Aristarque; Dompier, Thomas P; Kerr, Zachary Y
Abstract : Aim: To describe the epidemiology of National Collegiate Athletic Association (NCAA) men's and women's soccer injuries during the 2009/2010–2014/2015 academic years. Methods: This descriptive epidemiology study used NCAA Injury Surveillance Program (NCAA-ISP) data during the 2009/2010–2014/2015 academic years, from 44 men's and 64 women's soccer programmes (104 and 167 team seasons of data, respectively). Non-time-loss injuries were defined as resulting in <24 h lost from sport. Injury counts, percentages and rates were calculated. Injury rate ratios (RRs) and injury proportion ratios (IPRs) with 95% CIs compared rates and distributions by sex. Results: There were 1554 men's soccer and 2271 women's soccer injuries with injury rates of 8.07/1000 athlete exposures (AE) and 8.44/1000AE, respectively. Injury rates for men and women did not differ in competitions (17.53 vs 17.04/1000AE; RR=1.03; 95% CI 0.94 to 1.13) or practices (5.47 vs 5.69/1000AE; RR=0.96; 95% CI 0.88 to 1.05). In total, 47.2% (n=733) of men's soccer injuries and 47.5% (n=1079) of women's were non-time loss. Most injuries occurred to the lower extremity and were diagnosed as sprains. Women had higher concussion rates (0.59 vs 0.34/1000AE; RR=1.76; 95% CI 1.32 to 2.35) than men. Conclusions: Non-time-loss injuries accounted for nearly half of the injuries in men's and women's soccer. Sex differences were found in competition injuries, specifically for concussion. Further study into the incidence, treatment and outcome of non-time-loss injuries may identify a more accurate burden of these injuries.